No Link Between Date of Birth and ADHD Symptoms in Adults. (January 2014) - Kowalyk, Terra V.; Davis, Caroline; Wattie, Nick; Baker, Joseph
Objective: Research has highlighted several negative consequences for individuals born in the later part of the academic year, including increased likelihood of being diagnosed with learning disabilities. In this study, we considered whether birthdate predicted ADHD symptomatology using two well known mechanisms, the relative age effect (RAE) and the season of birth effect (SOBE). Methods: Study participants completed two ADHD measures: Conners Adult ADHD Rating Scales (CAARS) and the Wender Utah Rating Scale (WURS). Results: There were gender effects in the WURS data indicating that males scored higher than females on ADHD symptoms as well as a significant interaction in the CAARS data to support differential patterns among males and females. Conclusion: Overall, results did not support a RAE or SOBE among males or females. Possible reasons for these findings and their implications are discussed.